THEORETICAL ASPECTS OF OPTICAL RADIATION ENERGY ACTION ON STRUCTURE BIOLOGICALLY OBJECTS - Chervynskyy, L.; Romanenko, A.; Lutsak, J.; Nazarenko, I. (Енергетика і автоматика, 2016)
A Study teoretycheskoe photon optical radiation interaction with electrons obluchaemыh structures based on laws kvantovoy byofyzyky